Is the pandemic leading to a crisis of trust? Insights from an Italian nationwide study. (January 2022) - Gualano, M.R.; Lo Moro, G.; Voglino, G.; Bert, F.; Siliquini, R.
Abstract: Objectives: Along with mistrust toward politics and journalism, the pandemic is amplifying mistrust in healthcare. To explore trust in key professionals among the Italian population, we focused on perceived change in trust during the pandemic. Study design: Nationwide online cross-sectional survey (called COCOS). Methods: COCOS was conducted in Italy in two periods: the end of the first lockdown (T1: April–May 2020) and the end of 2020 (T2: November–December 2020). Descriptive analyses and multivariable logistic regressions were performed (sample size = 2673). Results: Trust in healthcare workers (HCWs) was reduced in 1.5% of participants (T1) and 2.8% (T2). Trust in scientists/researchers was reduced in 5.8% (T1) and 7.6% (T2). Trust in politicians was reduced in 37.6% (T1) and 52.3% (T2). Trust in journalists was reduced in 41.7% (T1) and 48.3% (T2). Considering multivariable models, participants of the second period, participants who were HCWs, participants with anxiety symptoms, and those experiencing economic struggle due to the pandemic had a higher likelihood of having a reduced trust. The period had the strongest association with reduced trust. Conclusions: We argue that a central role might be played by the pandemic fatigue. We suggest leading figures should be more aware of the relationship between communication and trust. The pandemic is a real-world experiment in reshaping mediated communication and, although social media play an important role, other approaches might be successful. As a notable part of the population is trusting politicians and media less and less, Italian key professionals should implement initiatives to reinvigorate public support.